2007
DOI: 10.1007/s12016-007-8036-z
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Non-Cystic Fibrosis Pediatric Bronchiectasis

Abstract: With the implementation of vaccination programs and the use of antibiotics, developed countries have seen a decline in infection-related pediatric bronchiectasis. However, significant morbidity from bronchiectasis is still seen and both infectious and noninfectious causes of bronchiectasis in the pediatric population remain. A review of the literature will be presented including causes of pediatric bronchiectasis, clinical symptoms and signs, laboratory evaluation and imaging, as well as treatment options. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 63 publications
1
27
0
1
Order By: Relevance
“…Bacterial pathogens were identified in the airways of all immunodeficient children with bronchiectasis and the most common isolates were Streptococcus pneumoniae, followed by Haemophilus influenzae and Pseudomonas aeruginosa, with the first microorganism associated with the most severe bronchiectasis. Similar results from sputum cultures from patients with non-cystic fibrosis bronchiectasis were reported in other investigations [18].…”
Section: Discussionsupporting
confidence: 90%
“…Bacterial pathogens were identified in the airways of all immunodeficient children with bronchiectasis and the most common isolates were Streptococcus pneumoniae, followed by Haemophilus influenzae and Pseudomonas aeruginosa, with the first microorganism associated with the most severe bronchiectasis. Similar results from sputum cultures from patients with non-cystic fibrosis bronchiectasis were reported in other investigations [18].…”
Section: Discussionsupporting
confidence: 90%
“…Here, we found that acidity in CF ASL is causal for increased ENaC cleavage/ activity and CF ASL volume depletion, suggesting that many of the defects in CF lung innate defense have a similar etiology, namely, reduced ASL pH. Gastric reflux is common in subjects with CF and has also been linked with lung disease in patients who do not have CF (30,31). Thus, in addition to the reduced pH caused by CFTR's absence, exposure of very low pH due to gastric reflux may further exacerbate this issue in patients with CF and contribute to a failure of mucus clearance in patients who do not have CF and are prone to gastric reflux.…”
Section: Discussionmentioning
confidence: 82%
“…Bronchiectasis is defined as an irreversible dilatation of the bronchi and is the end result of chronic inflammation and infection of the bronchi 19 (Fig. 9).…”
Section: Bronchiectasismentioning
confidence: 99%